Stakeholders perceptions of bioeconomy: a bibliometric analysis - Ribeiro, Maria Isabel (2022)
The Bioeconomy, in addition to being considered a means to achieve industrial competitiveness, offers new approaches to deal with future challenges, replacing fossil fuels with sustainable and renewable fuels and resources. A bibliometric study was carried out to describe the scientific production related to stakeholders’ perceptions about Bioeconomy and to group the existing literature into thematic clusters. 67 articles were selected from the Scopus database based on the words “Bioeconomy” and “Perceptions”. The VOSviewer software, version 1.6.18 was used to perform the bibliometric analysis. Four clusters were identified. The first cluster comprised the articles referring to the perceptions about the Bioeconomy of the timber sector stakeholders and of the different actors in the field of forestry action closest to the Bioeconomy area. The second cluster included articles related to the stakeholders’ perception of the Bioeconomy, namely, Civil Society in general and higher education students in particular, as well as their opinions on the importance of the forestry sector for the Bioeconomy. The third cluster comprised the articles that consider the Bioeconomy to be the innovative way to go to ensure the sustainability of the planet, therefore highlighting the importance of knowing the perceptions and raising awareness of all stakeholders to ensure the successful transition to the Bioeconomy. Finally, the fourth cluster included articles related to the perception of the Bioeconomy, consumer attitudes and behaviours regarding the acceptance of new biofood products resulting from the Circular Economy.